The Effect of Education through Short Message Service (SMS) Messages on Diabetic Patients Adherence - Adikusuma, Wirawan (Sci Pharm, 2017)
Poor adherence and a lack of understanding of medication instructions for oral antidiabetic use are key factors that inhibit the control of glycemic levels. The aforementioned situation needs intervention to improve medication adherence and the therapy. This study was conducted with a quasi-experimental design with prospective data collection. The subjects of this study were 50 outpatients with type 2 diabetes melitus (T2DM) who had received oral antidiabetic medicine therapy at least six months prior to adherence measurement. The patients were classified into two groups—the control group and the intervention group. The intervention group received Short Message Service (SMS) messages of diabetes education, while the control group did not. Data collection was conducted by doing interviews and administering the Morisky Medication Adherence Scale (MMAS) questionnaire. The results showed the increase in adherence in the intervention group as 1.15 ± 1.04 and that in the control group as 0.72 ± 0.90. These results indicated that there were significant differences in MMAS score between the control and intervention groups (p < 0.05). The decrease in fasting blood glucose and glucose measured 2 h postprandially was greater in the intervention group than that in the control group. It was concluded that the provision of education through SMS had a positive effect on medication adherence and glycemic levels.